Customer relationship management (CRM): The impact on SMEs performance - Siti Hajar, Mohamad; Norfaridatul Akmaliah, Othman; Izaidin, Abdul Majid; Juhaini, Jabar; Mastura, Roni (2013)
The Customer Relationship Management (CRM) strategy has become very popular among organizations and companies; hence it’s very common in large companies implement CRM to compete and promote their businesses. However, CRM strategies are not very common in Small and Medium Enterprises (SMEs). SMEs have to implement customer relationship into their business operations in order to strategies on establishing high performance and high value-added with strong technical, innovative capability and competitive advantage over rivals. CRM strategies have the potential to help improve the business value and competitive capabilities of SMEs, yet have received mixed performance reviews in the extant literature. Therefore, this research presents a conceptual model on the antecedents of achieving successful implementations of CRM strategies by Malaysian SMEs. The model incorporate CRM strategies construct; key customer focus, knowledge management, relationship marketing and technological CRM resources, and investigated the impact of CRM strategies on these constructs and relationship performance. In addition the firm’s market orientation has considered as critical antecedent to the practices of CRM. The model then enables several empirically testable propositions that are relevant to develop a survey instrument for this study.